2014
DOI: 10.1155/2014/534012
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study on the Methodology of Fast Imaging of Unilateral Stroke Lesions by Electrical Impedance Asymmetry in Human Heads

Abstract: Stroke has a high mortality and disability rate and should be rapidly diagnosed to improve prognosis. Diagnosing stroke is not a problem for hospitals with CT, MRI, and other imaging devices but is difficult for community hospitals without these devices. Based on the mechanism that the electrical impedance of the two hemispheres of a normal human head is basically symmetrical and a stroke can alter this symmetry, a fast electrical impedance imaging method called symmetrical electrical impedance tomography (SEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Clinical results specifically confirmed that there exists a statistically significant (P < 0.05) larger potential difference in the scalp potential distribution of patients suffering acute/subacute ICH than the controls, which, unlike simulated results, can be measured relatively fast (<1 h). Although these results are in agreement with the results from other numerical and experimental studies, 32,34,35,37,45,46 unlike previous experimental studies using stroke lesions from the chronic phase, i.e., lesions over a month old, 34,35,45 we obtained EIS recordings from patients in the acute and subacute phases, i.e., lesions less than five days old, to demonstrate the potential usefulness of EBI for the prehospital triage of patients suffering acute/subacute brain injury.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Clinical results specifically confirmed that there exists a statistically significant (P < 0.05) larger potential difference in the scalp potential distribution of patients suffering acute/subacute ICH than the controls, which, unlike simulated results, can be measured relatively fast (<1 h). Although these results are in agreement with the results from other numerical and experimental studies, 32,34,35,37,45,46 unlike previous experimental studies using stroke lesions from the chronic phase, i.e., lesions over a month old, 34,35,45 we obtained EIS recordings from patients in the acute and subacute phases, i.e., lesions less than five days old, to demonstrate the potential usefulness of EBI for the prehospital triage of patients suffering acute/subacute brain injury.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the limitations of the study, like the low statistical power, the obtained results agree with previous bioimpedance-related studies. 32,34,35,37,45,46 The results indicate that a hemorrhagic brain lesion generates spatial changes in voltage, which can be recorded directly on scalp, thus supporting this type of bioimpedance technology for potential early detection of brain ICH.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Consequently, a portable and inexpensive diagnostic tool to detect stroke quickly, which can be used in primary healthcare units and ambulances, is urgently needed. Because biological tissues have different impedance characteristics under normal physiological conditions and different pathological states [5,6,7,8], impedance methods are proposed to detect stroke [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Second, because the impedance distribution of both brain hemispheres of normal human is symmetrical, whereas it is otherwise for a stroke patient, it is possible to detect stroke by comparing whether the impedance distribution is symmetrical for the hemispheres in a subject’s head [17,18,19,20]. This method requires that the shape of the subject’s two hemispheres should be basically symmetrical and that the electrodes must be strictly placed [18]. Third, since normal brain tissues and stroke lesions have different spectra, the impedance distribution inside the subject’s head can be reconstructed in order to detect stroke.…”
Section: Introductionmentioning
confidence: 99%